Objective Structured Clinical Examination (OSCE): Relevance and Feasibility of an Objective Way of Student’s Assessment in Community Medicine - Naik, Bijaya; Kanungo, Srikanta; Reddy, Mahendra M (National Journal of Community Medicine, 2019)
The proposed competency based medical curriculum to be implemented from academic year 2019-20 by Medical Council of India (MCI) envisages the medical graduates to acquire requisite competency and skills to address the health issue of the country. Appropriate assessment methods should be devised in line with curriculum objectives to bring best out of the medical graduates as per the needs of the country. Community medicine, which is concerned with the holistic health care of the community, trained medical students to be primary health care provider with leadership skills. The traditional methods of assessment in community medicine focuses mainly recall type of answer with little scope for interpretation, application and demonstration of skills. Thereby, it fails to inculcate requisite competency and skills for effective primary health care delivery. OSCE, which is a validated tool in other medical branches for skill improvement, can be adopted in formative as well as summative assessment of medical graduates in community medicine. This method of assessment not only will improve the skill and competency of medical graduates in community medicine for effective delivery of primary health services but also generate interest in the subjects.